The Complete Genome Sequence of Hyperthermophile Dictyoglomus turgidum DSM 6724™ Reveals a Specialized Carbohydrate Fermentor - Brumm, Phillip J.; Gowda, Krishne; Robb, Frank T.; Mead, David A. (Frontiers in Microbiology, 2016)
Here we report the complete genome sequence of the chemoorganotrophic, extremely thermophilic bacterium, Dictyoglomus turgidum, which is a Gram negative, strictly anaerobic bacterium. D. turgidum and D. thermophilum together form the Dictyoglomi phylum. The two Dictyoglomus genomes are highly syntenic, and both are distantly related to Caldicellulosiruptor spp. D. turgidum is able to grow on a wide variety of polysaccharide substrates due to significant genomic commitment to glycosyl hydrolases, sixteen of which were cloned and expressed in our study. The GH5, GH10 and GH42 enzymes characterized in this study suggest that D. turgidum can utilize most plant-based polysaccharides except crystalline cellulose. The DNA polymerase I enzyme was also expressed and characterized. The pure enzyme showed improved amplification of long PCR targets compared to Taq polymerase. The genome contains a full complement of DNA modifying enzymes, and an unusually high copy number (4) of a new, ancestral family of polB type nucleotidyltransferases designated as MNT (minimal nucleotidyltransferases). Considering its optimal growth at 72ºC, D. turgidum has an anomalously low G+C content of 39.9% that may account for the presence of reverse gyrase, usually associated with hyperthermophiles.